Sequence requirement for expression of the Drosophila melanogaster heat shock protein hsp22 gene during heat shock and normal development. - Klemenz, R (1986)
A 14-base-pair sequence element present in almost all Drosophila melanogaster heat shock genes has been implicated in the heat inducibility of transcription. The D. melanogaster gene encoding the smallest heat shock protein, hsp22, contains within its 5' flanking sequences three such repeats, two close to the transcription start site and a distally located third one 101 base pairs further upstream. Deletion analyses reveal that the 5' flanking sequences required for full expression of the hsp22 gene extend beyond the distal repeat. Deletion of the furthest upstream repeat results in a five to sixfold reduction of gene expression. The small heat shock genes are transiently expressed in the late third instar larval and early pupal stages without external stimulation. A deletion of 5' flanking sequences to position -194, which includes two nucleotides of the distal heat shock element, has no effect on the developmental expression, whereas removal of an additional 18 nucleotides, including 12 nucleotides of the distal heat shock element, severely reduces developmental expression.